A new Pteroncola (Bacillariophyceae) from the South Shetland Islands (Antarctica) - Almandoz, Gaston Osvaldo; Ferrario, Martha Elba; Sullivan, Michael J.; Ector, Luc; Schloss, Irene Ruth
The marine araphid diatom Pteroncola pottercovei sp. nov. is described for a coastal Antarctic environment, based on light and scanning electron microscopy observations. The new species was found as solitary cells in the phytoplankton and epiphytic on the chains of other diatoms. It can be distinguished from P. inane, the only recognized species of the genus up to now, mainly by the presence of a well developed sternum and a hyaline mantle, apical pore fields composed of three horizontal rows of pores, a single rimoportula per valve, and a lower striae density. Two morphotypes could be distinguished in relation to the ultrastructure of alveolate (chambered) striae in external view. While most specimens presented striae formed by transapically elongated slits others showed striae composed of a row of small areolae. An emended description of Pteroncola is provided as well as a comparison with related genera in the Fragilariaceae, such as Brandinia, Catacombas, Hyalosynedra, Fragilaria, Fossula, Staurosirella and Thalassioneis. Fil: Almandoz, Gaston Osvaldo. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Ferrario, Martha Elba. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Sullivan, Michael J. No especifica; Fil: Ector, Luc. Public Research Centre. Department of Environment and Agro-biotechnologies; Luxemburgo Fil: Schloss, Irene Ruth. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Université du Québec à Rimouski; Canadá